Helically chiral π-expanded azocines through regioselective Beckmann rearrangement and their charged states - Borstelmann, Jan; Schneider, Lars; Rominger, Frank; Deschler, Felix; Kivala, Milan (Angewandte Chemie. International edition, 2024)
We report a synthetic approach to π-expanded [6]helicenes incorporating tropone and azocine units in combination with a 5-membered ring, which exhibit intriguing structural, electronic, and chiroptical properties. The regioselective Beckmann rearrangement allows the isolation of helical scaffolds containing 8-membered lactam, azocine, and amine units. As shown by X-ray crystallographic analysis, the incorporation of tropone or azocine units leads to highly distorted [6]helicene moieties, with distinct packing motifs in the solid state. The compounds exhibit promising optoelectronic properties with considerable photoluminescence quantum yields and tunable emission wavelengths depending on the relative position of the nitrogen center within the polycyclic framework. Separation of the enantiomers by chiral high-performance liquid chromatography (HPLC) allowed characterization of their chiroptical properties by circular dichroism (CD) and circularly polarized luminescence (CPL) spectroscopy. The azocine compounds feature manifold redox chemistry, allowing for the characterization of the corresponding radical anions and cations as well as the dications and dianions, with near-infrared (NIR) absorption bands extending beyond 3000 nm. Detailed theoretical studies provided insights into the aromaticity evolution upon reduction and oxidation, suggesting that the steric strain prevents the azocine unit from undergoing aromatization, while the indene moiety dominates the observed redox chemistry.
Zuerst veröffentlicht: 08. Mai 2024
Gesehen am 14.11.2024